The inhibitory effect of Saccharomyces cereviisiiae filtrates on the growth of biofilm-forming Staphylococcus aureus (Journal of the College of Basic Education, 2023)
The study included an investigation of the inhibitory ability of yeast isolates6 p.a. (obtained from commercial sourcesimported) on the growth of Staphylococcus aureus isolated from diseased casesdifferent, as it was possible to obtain (01) isolates of the bacterium A. Sa’az {Hartmeh: K.All these isolates were subjected to culture, microscopic and biochemical examinations and were diagnosedusing the 714662 system. The ability of the isolates to form a biofilm was tested usingTwo methods are the center of the solid Congo Red ( ) APM andAccurate calibration dishes method (17) 0 L Mohan, hasThe results showed that the second method was the most sensitive in investigating membrane formationbiofilm, where (60%) of the isolates showed their ability to form a biofilm in a manner(H) and (83.3%) by the method of (7) and the other isolates did not produce a biofilm.Regarding the sensitivity test, these isolates showed variation in their resistance to antibioticsThe biosynthesis is under study, with the exception of the similarity of all isolates in their resistance to pathogenesisL and 21007710, with a percentage of 100%, and its sensitivity is 100% for an antidote.